2017
DOI: 10.1093/cvr/cvx244
|View full text |Cite
|
Sign up to set email alerts
|

Normal interventricular differences in tissue architecture underlie right ventricular susceptibility to conduction abnormalities in a mouse model of Brugada syndrome

Abstract: AimsLoss-of-function of the cardiac sodium channel NaV1.5 is a common feature of Brugada syndrome. Arrhythmias arise preferentially from the right ventricle (RV) despite equivalent NaV1.5 downregulation in the left ventricle (LV). The reasons for increased RV sensitivity to NaV1.5 loss-of-function mutations remain unclear. Because ventricular electrical activation occurs predominantly in the transmural axis, we compare RV and LV transmural electrophysiology to determine the underlying cause of the asymmetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The authors suggested that normal structural heterogeneities present in the RV are responsible for increased vulnerability to conduction slowing in the presence of reduced sodium channel function (Kelly et al. ). Alternatively, other studies have shown lower Na + channel expression in the RVOT compared to the RV and have implicated the RVOT as the main origin of arrhythmias in BrS (Boukens et al.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that normal structural heterogeneities present in the RV are responsible for increased vulnerability to conduction slowing in the presence of reduced sodium channel function (Kelly et al. ). Alternatively, other studies have shown lower Na + channel expression in the RVOT compared to the RV and have implicated the RVOT as the main origin of arrhythmias in BrS (Boukens et al.…”
Section: Discussionmentioning
confidence: 99%
“…Using histology and two-photon microscopy, the RV wall of the mouse heart was previously found to be occupied by a higher number of non-vascular clefts, also of a bigger size, compared with the mouse LV wall [ 32 ]. This difference in tissue architecture was not accompanied by a significant difference in fibrosis levels [ 32 ].…”
Section: The Right Ventricular Outflow Tractmentioning
confidence: 99%
“…Using histology and two-photon microscopy, the RV wall of the mouse heart was previously found to be occupied by a higher number of non-vascular clefts, also of a bigger size, compared with the mouse LV wall [ 32 ]. This difference in tissue architecture was not accompanied by a significant difference in fibrosis levels [ 32 ]. Although the number and size of intramural clefts may affect the normal pathway of conduction in the RV and thereby cause a delay in transmural activation or conduction block, several key questions remain unanswered.…”
Section: The Right Ventricular Outflow Tractmentioning
confidence: 99%
“…Indeed, a murine heterozygous SCN5A+/− model was generated for BrS in vivo studies ( Papadatos et al, 2002 ). This model has been used by several groups to mimic BrS, demonstrating how the SCN5A haploinsufficiency was responsible for the onset of a complex range of phenotypes, including a 50% reduction of sodium conductance, a delayed intramyocardial conduction, a sinus node dysfunction, and ventricular arrhythmogenesis, which are hallmarks of BrS patients ( Zhang et al, 2014 ; Tse et al, 2017 ; Kelly et al, 2018 ). However, caution must be made when translating the results of action potential studies in murine models to the situation in humans, as many differences exist between the species ( Milani-Nejad and Janssen, 2014 ).…”
Section: The Genetics Of Brugada Syndrome: Ion Channel Sarcomeric Amentioning
confidence: 99%